Household Solid Waste Management Practices in Low-Income Suburbs in Kaduna North and South Local Government Areas of Kaduna State, Nigeria - James, Amos Akpokos; Baduku, Silas Anthonia; Umar, Mal. Ahmed (NIU Journal of Social Sciences, 2025)
The recent surge in the volume of household solid waste generation especially in Sub-Saharan Africa has become a major public health concern as it poses severe health, safety and environmental consequences to the public. Given these concerns, this study investigated household solid waste disposal or management practices among residents of low-income suburbs in Kaduna metropolitan area. Questionnaire survey was used to elicit the required information from 450 household heads, selected from six (6) low-income suburbs in the study, using the systematic sampling technique. Descriptive statistics such as frequency distribution and percentages as well as chi-square test were employed for data analysis. The findings showed that food scrap is mentioned as the most generated waste by 65.1% of the respondents. This is followed by products packaging (63.8%) and rubber/plastic or polythene (55.3%).  The study also showed that 47.2% of the respondents disclosed that they generate less than 1kg of waste daily and that household waste according to 59.5% and 26.0% are disposed mainly at open refuse dumps and by way of burning respectively. Additionally, 48.8% of the respondents stated that household heads/tenants are solely responsible for disposing their accumulated waste. This study recommends that practical skills on how food debris can be converted to manure or compost should be taught   to residents and a system of waste collection which will utilize the services of private waste collectors and individuals should be put in place by the communities and other relevant stakeholders. Keywords: Household, Low-income, Management, Neighbourhoods, Practices